RETRACTED: The HBV Core Protein and Core Particle Both Bind to the PPiase Par14 and Par17 to Enhance Their Stabilities and HBV Replication - Saeed, Umar; Piracha, Zahra Zahid; Kwon, Hyeonjoong; Kim, Jumi; Kalsoom, Fadia; Chwae, Yong-Joon; Park, Sun; Shin, Ho-Joon; Lee, Hyun Woong; Lim, Jin Hong; Kim, Kyongmin (Frontiers in Microbiology, 2021)
We recently reported that the PPIase Par14 and Par17 encoded by PIN4 upregulate HBV replication in an HBx-dependent manner by binding to conserved arginine–proline (RP) motifs of HBx. HBV core protein (HBc) has a conserved 133RP134 motif; therefore, we investigated whether Par14/Par17 bind to HBc and/or core particles. Native agarose gel electrophoresis (NAGE) and immunoblotting and co-immunoprecipitation were used. Chromatin immunoprecipitation from HBV-infected HepG2-hNTCP-C9 cells were performed. NAGE and immunoblotting revealed that Par14/Par17 bound to core particles and co-immunoprecipitation revealed that Par14/Par17 interacted with core particle assembly-defective, dimer-positive HBc-Y132A. Thus, core particles and HBc interact with Par14/Par17. Par14/Par17 interacted with the HBc 133RP134 motif possibly via substrate-binding E46/D74 and E71/D99 motifs. Although Par14/Par17 dissociated from core particles upon heat treatment, they were detected in 0.2 N NaOH-treated opened-up core particles, demonstrating that Par14/Par17 bind outside and inside core particles. Furthermore, these interactions enhanced the stabilities of HBc and core particles. Like HBc-Y132A, HBc-R133D and HBc-R133E were core particle assembly-defective and dimer-positive, demonstrating that a negatively-charged residue at position 133 cannot be tolerated for particle assembly. Although positively-charged R133 is solely important for Par14/17 interactions, the 133RP134 motif is important for efficient HBV replication. Chromatin immunoprecipitation from HBV-infected cells revealed that the S19 and E46/D74 residues of Par14 and S44 and E71/D99 residues of Par17 were involved in recruitment of 133RP134 motif-containing HBc onto cccDNA. Our results demonstrate that interactions of HBc, Par14/Par17, and cccDNA in the nucleus and core particle–Par14/Par17 interactions in the cytoplasm are important for HBV replication.